Discovering monoacylglycerol lipase inhibitors by a combination of fluorogenic substrate assay and activity-based protein profiling - Deng, Hui; Zhang, Qianwen; Lei, Qian; Yang, Na; Yang, Kai; Jiang, Jianbing; Yu, Zhiyi (Frontiers in Pharmacology, 2022)
The endocannabinoid 2-arachidonoylglycerol (2-AG) is predominantly metabolized by monoacylglycerol lipase (MAGL) in the brain. Selective inhibitors of MAGL provide valuable insights in the role of 2-AG in a variety of (patho)physiological processes, and are potential therapeutics for the treatment of diseases such as neurodegenerative disease, inflammation, pain, as well as cancer. Despite a number of MAGL inhibitors have been reported, inhibitors with new chemotypes are still required. Here, we developed a substrate-based fluorescence assay by using a new fluorogenic probe AA-HNA and successfully screened a focused library containing 320 natural organic compounds. Furthermore, we applied activity-based protein profiling (ABPP) as an orthogonal method to confirm the inhibitory activity against MAGL in the primary substrate-based screening. Our investigations culminated in the identification of two major compound classes, including quinoid diterpene (23, cryptotanshinone) and β-carbolines (82 and 93, cis- and trans-isomers), with significant potency towards MAGL and good selectivity over other 2-AG hydrolases (ABHD6 and ABHD12). Moreover, these compounds also showed antiproliferative activities against multiple cancer cells, including A431, H1975, B16-F10, OVCAR-3 and A549. Remarkably, 23 achieved complete inhibition towards endogenous MAGL in most of cancer cells determined by ABPP. Our results demonstrate the potential utility of the substrate-based fluorescence assay in combination with ABPP for rapid discovering MAGL inhibitors, as well as providing an effective approach to identify potential targets for compounds with significant biological activities.